Development of Theory of Economic Diplomacy in Russia in 2000-2018: Scientometric and Institutional Analysis - R. O. Raynkhardt (Научный диалог, 2019)
The development of theoretical research in the field of economic diplomacy, state support of national business in its entry into foreign markets in Russia at the latest stage is considered. The relevance of the topic is determined by the fact that, despite the significant general scientific reserve in this area, it still shows a tendency to disparate development by both research centres and individual scientists specializing in it. The latter often have a rather poor understanding of the progress and results of specialized research conducted by their colleagues. At the same time, it is the scientific community that is seen as one of the backbone elements of the national economic and diplomatic complex, whose activities are designed to smooth out the contradictions between state bodies, on the one hand, and representatives of the business community, on the other hand. Thus, the consolidation of relevant research centres, competition between them, as well as the overall development of this practice-oriented theoretical direction by its nature are the key to improving the efficiency of Russian foreign policy. On this basis, through the scientometric analysis of methods and tools adapted to the goals and objectives of the project, an institutional map of the scientific community involved in economic diplomacy was drawn up. According to the results of this analysis, a number of trends were identified: the preservation of the positions of institutes and scientific schools traditionally specializing in this area (MGIMO, Diplomatic Academy), the gradual emergence of new participants in this subgroup of the scientific community, the virtual absence of works in this direction in a number of organizations that have objective prerequisites for this, a strong personification of research (the predominance of the scientist’s personality factor over institutional factors), the isolation of the scientific and expert community on itself with weak communication between its individual members at all levels. The revealed phenomena testify to the structural difficulties of institutional development of the scientific community as an agent of economic diplomacy in Russia at the latest stage. An adequate response to the relevant challenges requires further research into each of the described elements of the scientific infrastructure, which can contribute to the development of an overall strategy by decision makers in the field of scientific and economic policy.